Identification of Novel Phage Resistance Mechanisms in Campylobacter jejuni by Comparative Genomics - Sørensen, Martine C. H.; Gencay, Yilmaz Emre; Fanger, Florian; Chichkova, Mariana A. T.; Mazúrová, Mária; Klumpp, Jochen; Nielsen, Eva M.; Brøndsted, Lone (Frontiers in Microbiology, 2021)
Phages infecting Campylobacter jejuni are considered a promising intervention strategy at broiler farms, yet phage sensitivity of naturally occurring poultry isolates is not well studied. Here we investigated phage sensitivity and identified resistance mechanisms of C. jejuni strains originating from Danish broilers belonging to the most prevalent MLST (ST) types. Determining plaque formation of 51 phages belonging to Fletchervirus or Firehammervirus showed that 21 out of 31 C. jejuni strains were susceptible to at least one phage. While C. jejuni ST-21 strains encoded the common phase variable MeOPN receptor of the Fletchervirus and were only infected by these phages, ST-45 strains did not encode this receptor and were exclusively infected by Firehammervirus phages. To identify internal phage resistance mechanism in ST-21 strains, we performed comparative genomics of two strains, CAMSA2002 sensitive to almost all Fletchervirus phages and CAMSA2038, resistant to all 51 phages. The strains encoded diverse CRISPR spacers but none matched the tested phages. Sequence divergence was also observed in a predicted SspE homolog and putative restriction modification systems including a methyl-specific McrBC endonuclease. Furthermore, when mcrB was deleted, CAMSA2038 became sensitive to 17 out of 43 phages, three being Firehammervirus phages that otherwise did not infect any ST-21 strains. Yet, 16 phages demonstrated significantly lower efficiencies of plating on the mcrB mutant suggesting additional resistance mechanism still restricting phage propagation in CAMSA2038. Thus, our work demonstrates that C. jejuni isolates originating from broilers may have acquired several resistance mechanisms to successfully prevent phage infection in their natural habitat.